2012
DOI: 10.1111/j.1558-5646.2012.01727.x
|View full text |Cite
|
Sign up to set email alerts
|

POLLINATOR-MEDIATED REPRODUCTIVE ISOLATION AMONG DIOECIOUS FIG SPECIES (FICUS, MORACEAE)

Abstract: Seed development and seedling growth were largely comparable between conspecific and heterospecific crosses. Heterospecific pollinator fitness, however, was significantly less than that of conspecific pollinators. Heterospecific pollinators induced gall formation but offspring did not develop to maturity in the new host. Selection on pollinators maintaining host specificity appears to be an important mechanism of contemporary reproductive isolation among these taxa that could potentially influence their divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 69 publications
2
47
0
1
Order By: Relevance
“…R. Soc. B 283: 20152963 shifts, as shown here and in previous studies [13,14,23,32,33], suggest hybridization and introgression among symmetric fig species should be a natural outcome of pollinator sharing.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…R. Soc. B 283: 20152963 shifts, as shown here and in previous studies [13,14,23,32,33], suggest hybridization and introgression among symmetric fig species should be a natural outcome of pollinator sharing.…”
Section: Discussionsupporting
confidence: 78%
“…The pollinator sharing ratio may be overestimated with wasps collected from receptive syconia if wasps have lower survival on 'non-typical' hosts, compared with the ratio calculated based on wasps emerging from syconia in the male flower phase [14]. The high pollinator sharing ratio within F. auriculata complex may be partially explained by this reason, as all pollinators of FA and half the pollinators of FO were collected from receptive syconia (electronic supplementary material, table S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, contrary to the expectation under strict cospeciation, where speciation events of interacting lineages occur at the same time (Huelsenbeck, Rannala, & Larget, ). Moe and Weiblen () and Yu et al () have proposed faster speciation rates for wasps than their host figs, suggesting that occasional breakdowns in the one‐to‐one matching might be inevitable. While each of these studies provides useful insights, the results are hard to compare, as they span different regions, taxa, and different phases of the cospeciation process.…”
Section: Introductionmentioning
confidence: 99%
“…Although many plant groups experience frequent hybridization events during their evolution [13] [14], Ficus is usually considered an exception because of its specific pollination mode [2]. However, recent estimations from genetic data on six sympatric dioecious fig species in New Guinea suggested that 12% of fig populations included hybrids [15]. Conversely, the genetic identities of sympatric fig species were strictly maintained though fig-wasp species were shared among them [16].…”
Section: Introductionmentioning
confidence: 99%